Pendampingan Persiapan Menuju Pendaftaran Tanah Sistematis Lengkap Di Desa Matangaji - Gusti Yosi Andri (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Community enthusiasm decreased when the legalization program initiated by the Government failed to be implemented well in Matangaji village, Cirebon Regency. The purpose of this writing is to regenerate people's interest to register land. The method used is by providing counseling and mentoring. The results of the research show that the majority of the Matangaji village community is no longer interested in registering their land. They think that having controlled a piece of land for a long time, since elder generation, is sufficient as an owner even though they don’t have land certificate. Counseling and mentoring provided by KKN students, limited knowledge and lack of legal awareness regarding the importance of proof of ownership of land rights began to gradually disappear. Mentoring is a differentiating factor because the community feels helped to fulfill land registration requirements. The people of Matangaji village hope that the PTSL program will soon be carried out again.